Azithromycin-Containing Regimens for Treatment of Mycobacterium avium Complex Lung Disease - Griffith, David E.; Brown, Barbara A.; Girard, William M.; Griffith, Bryan E.; Couch, Leslie A.; Wallace, Richard J. (Clinical infectious diseases, 2001)
Ninety-two patients were assessable in 3 consecutive, open, noncomparative, prospective, controlled, single-center trials of the use of multidrug regimens that contain azithromycin for treating pulmonary Mycobacterium avium complex (MAC) disease. Azithromycin was provided at a dose of 300-600 mg per day with oral companion drugs administered daily (regimen A, 29 patients); 600 mg 3 times weekly (t.i.w.), with oral companion drugs administered daily (regimen B, 20 patients); and 600 mg t.i.w., with oral companion drugs administered t.i.w. (regimen C, 43 patients). All regimens included rifabutin (or rifampin) and ethambutol as companion drugs as well as initial streptomycin. Treatment success was defined as 12 months of negative cultures while on therapy. Treatment failure was defined as sputum culture positivity after at least 6 months of therapy. Of the patients in each regimen who reached study end points, 17 of 29 (59%) were in regimen A, 11 of 20 (55%) were in regimen B, and 28 of 43 (65%) were in regimen C met the treatment success criterion. There were no statistically significant differences in outcome between the 3 regimens. These studies demonstrate the effectiveness of daily and t.i.w. regimens containing azithromycin for treatment of MAC lung disease.